Efeito preventivo da desmineralização do esmalte com materiais seladores aplicados em fissuras oclusais de molares humanos : estudo in situ - Poleto, Laís Caroline (2015)
This in situ study evaluated the preventive effect, on the desminaralization of enamel, of a resin sealant and a resin modified glass ionomer cement. Specimens of the occlusal third molars were divided into six groups: 1- Vitremer® with biofilm, 2- Vitremer® without biofilm, 3- Alpha Seal® with biofilm, 4- Alpha Seal® without biofilm, 5- control with biofilm, 6 - control without biofilm. During a 21-day trial, 10 volunteers wore palatal devices (24h/day) and 8x/day dropped a 20% sucrose solution in all the blocks. The oral hygiene was done after meals, and the cleaning of device was done only in the non-display side (toothpaste 1500 ppmF 3x/day). After the experiment, the blocks were sectioned for longitudinal microhardness at distances of 10, 20, 30, 60, 90 and 200μm enamel surface in four rows: under the sealant (internal 100μm), in the edge of the material and two external rows (100μm and 200μm). Variance Analysis (ANOVA) with repeated measures and Tukey's test showed the difference in 10μm for material factor (p=0.003) and row factor (p=0.018), while in 20μm analysis was difference in the material factor (p=0.015), row factor (p=0.029) and biofilm factor (p= 0.006). In 30μm was difference to the material factor (p=0.002), row factor (p=0.047) and biofilm factor (p=0.034). The groups sealed with Vitremer® showed higher hardness values (p<0.05). The hardness was significantly different among the different depths (10 < 20 < 30 < 60 = 90/200) (p<0.05). The biofilm interfered significantly in hardness and materials behavior. This study shows that sealing materials provide a preventive effect for desmineralization, and may be an alternative of treatment for patients with high-risk caries, with better indication for materials with fluoride in composition.